Artificial Intelligence and Digital Competence in Digital HRM: How Educational Collaboration Moderates HR Effectiveness - Purjianto Purjianto; Sri Wahyuni (JUMPA : Jurnal Manajemen Pendidikan, 2026)
The rapid advance of digital transformation has positioned Artificial Intelligence as a decisive force in reshaping human resource management, yet its value depends not on technology alone but on the digital competence of human resources and the systems through which both are operationalised. Existing studies tend to examine technology and competence separately, and they rarely account for the role of education in cultivating the digital readiness that effective digital human resource management requires. This study aims to develop and test an integrated model of Digital Human Resource Management grounded in Artificial Intelligence in order to explain the effectiveness of human resource management within the context of collaboration between organisations and the educational sector. The study employed a quantitative approach with an explanatory design, drawing on data from 150 respondents comprising human resource practitioners, managers, and academics selected through purposive sampling. The data were analysed using Partial Least Squares Structural Equation Modeling with the assistance of SmartPLS. The results demonstrate that artificial intelligence and digital competence both exert significant positive effects on digital human resource management, which in turn produces the strongest direct effect on human resource effectiveness, while the two antecedents also influence effectiveness directly to a lesser degree. These findings position digital human resource management as the central construct linking technological capability and digital competence to organisational effectiveness. The implications of this study indicate that organisations should embed artificial intelligence investment within mature digital human resource systems and prioritise the cultivation of digital competence through collaboration with education as a strategic foundation of effectiveness.